Motherhood and Work in Chile: Current discourses of stakeholders (Polis (Santiago), 2018)
The relationship between motherhood and work has been a public policy topic since the early twentieth century, but in recent decades this relation has taken on new connotations due to the increase in female labor force participation. This has not led to an elimination of the discrimination of female workers because of their status as real or potential mothers, or to an organization of the labor market that allows harmonizing work and family demands, or to a redistribution of reproductive work. To analyze how actors involved in policy formulation face this issue, how they understand the relationship between work and motherhood and the tensions that arise from it, a group of stakeholders from three areas were interviewed. Two ideas characterize their conceptions: the rules of maternity protection at work affect adversely the employability of women; and the relationship work-motherhood is hard because the organization of the labor market makes difficult to articulate work and family responsibilities. There were identified some specific tensions in different areas: economic, demographic, socio-cultural and exercise of rights.
Keywords: motherhood; work; health; stakeholders